Thomas - Pryor, Bonnie; Dodson, Bert (New York : Morrow Junior Books, 1998)
In the early years of the Revolutionary War, Thomas and his family escape a bloody massacre at Wyoming Valley and endure innumerable hardships as they try to make their way to Philadelphia.
690
690
Accelerated Reader AR
Keywords: Frontier and pioneer life -- Pennsylvania -- Fiction; Pennsylvania -- History -- Revolution -- Fiction; Pennsylvania -- History -- Revolution, 1775-1783 -- Juvenile fiction; United States -- History -- Revolution, 1775-1783 -- Juvenile fiction